Produção e caracterização de uma proteína recombinante multiepitopica Loxoscelica (rMEPLox) expressa em plantas (Arabidopsis thaliana) - María José González Armijos (2021)
The venom of spiders of the genus Loxosceles is mainly composed of a rich mixture of metalloproteinases, phospholipases and sphingomyelinases. Currently, there are several studies for the production of anti-poisons, using recombinant proteins, in order to persevere the life of animals that produce the poison (spiders) and also animals that produce serum, since this poison is very toxic. For this reason, this work aimed to express and characterize rMEPLox, a recombinant protein composed of epitopes of the three main toxins from spider’s venoms of the genus Loxosceles spp., In plants as a new heterologous expression system. Initially, the rMEPLox gene was transferred from the expression vectors to E. coli in a plant-specific plasmid vector (pMDC32). Then, Agrobacterium tumefaciens was transformed with these vectors and these plant-specific bacteria were able to infect Arabidopsis thaliana through floral immersion. The plants were cultivated and reproduced until the third generation (T3) was obtained, to obtain totally homozygous populations. The total proteins were extracted from A. thaliana and the protein content was analyzed by SDS-PAGE, ELISA and Western Blotting. In immunoassays, they suggest that the protein extracts were recognized by the anti- rMEPLox serum, previously produced in E. coli. Through Western blotting it was possible to observe the presence of protein bands of approximately 19 kDa, the same molecular mass as rMEPLox. These results lead us to confirm the success of the transformations for A. thaliana; and that plants express the rMEPLox protein.